Identificação e caracterização molecular do ácaro-azul-das-pastagens (Penthaleus major) no Brasil - Castilhos, Lauren Brondani (2023)
The blue oat mite, Penthaleus major (Dugés) (Penthaleidae), is a widely distributed pest worldwide. The damage caused by this mite is due to its feeding habits, causing laceration of the epidermis and removal of chlorophyll from the cells, resulting in a silver appearance in plants and reduced height. In Brazil, Penthaleus major was detected attacking oat plants for grazing on a private property located between the municipalities of André da Rocha and Protásio Alves, Rio Grande do Sul, in the year 2009. After a period without reports of occurrence, in 2020, in the municipalities of André da Rocha and Cachoeira do Sul (RS), mites were found again on private properties, also in oat pastures. This work aimed to document and performed the identification and molecular characterization of this species in order to confirm the presence of the blue grass mite in Brazil. Therefore, specimens of these mites were collected and subjected to genomic DNA extraction and PCR techniques for the amplification of the mitochondrial gene cytochrome oxidase I (COI). The study confirmed the introduction and presence of the species Penthaleus major in Brazil through molecular identification, ensuring greater accuracy and reliability in the identification of this species.